Public Wages, Public Employment, and Business Cycle Volatility: Evidence from U.S. Metro Areas - Claire A. Boeing-Reicher; Vincenzo Caponi (Institute for the Study of Labor (IZA), 2016)
Based on data from a cross section of U.S. metro areas, we show that public employment correlates negatively with business cycle volatility, hinting at a stabilizing effect of public employment, while public wages correlate weakly and positively with business cycle volatility, hinting at a destabilizing effect of public wages. To explain these relationships, we set up a search and matching model that contains a government sector and a role for government spending in product markets. This latter mechanism affects how the outside option behaves, and this mechanism can help a search and matching model to generate wage-reducing and stabilizing effects of public employment. Without this mechanism, a search and matching model cannot generate these effects.
Keywords: E32; E63; J21; 330; public employment; public wages; business cycle volatility; crowding out; search and matching